An Analytical Study of the Literary Work Phra Ananda, the Buddha’s Younger Brother by Wasin Inthasara - (Chaisuwan), PhraNiphon Thhantajitto; Silsrathikhun, Phrakhru (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to 1) examine the concept of literature 2) study the literary work Phra Ananda, the Younger Brother of the Buddha by Wasin Inthasara, and 3) analyze the values and practices reflected in the work. This study employed a qualitative documentary research approach by collecting data from the Thai Tipitaka, Buddhist texts, and related academic documents, which were then analyzed using content analysis. The findings revealed that 1) literature plays a significant role in Thai society as a medium for transmitting moral teachings, reflecting social conditions, and motivating ways of life 2) the literary work Phra Ananda, the Younger Brother of the Buddha possesses literary and Buddhist philosophical value, presenting the biography and virtues of Phra Ananda through refined and accessible prose 3) the practical analysis demonstrates that Phra Ananda serves as a model of conduct that generates benefits on three levels: self-benefit through the attainment of arahantship, benefit to others particularly through supporting the ordination of nuns and benefit to Buddhism through his important role in establishing the Vinaya and participating in the First Buddhist Council.